Occurrence of Twin Seedlings in Cynometra travancorica Bedd.-An Endangered Tree Species of Western Ghats, India - Sringeswara, A. N.; Vishwanath, Sahana; Rajanna, M. D. (Indian Forester, 2015)
No Abstract.